Yeast killer toxins and dimorphism. - Polonelli, L (1989)
The differential action of four selected yeast killer toxins on the mycelial and yeast forms of four isolates of the dimorphic fungus Sporothrix schenckii was comparatively evaluated. The results confirmed that the yeast killer phenomenon is present among hyphomycetes and yeasts and that both morphological forms of S. schenckii are susceptible to the action of the same yeast killer toxin. Quantitative differences in the response to the killer action of the mycelial and yeast forms in individual strains were also observed. To avoid retroconversion of the dimorphic forms, we used a modification of the conventional killer system.